IMMUNE THERAPY OF ENTEROVIRUS MENINGITIS IN CHILDREN - Yu. B. Hamanova (Detskie Infekcii (Moskva), 2015)
The authors analyzed 254 cases of Enteroviral Meningitis (EVM) in children that were treated in the children's department of neuroinfections ofClinicalHospital№40 inClinical andDiagnosticCenter. We compared the conventional method of the treatment of EVM in children above three years with complex therapy that includes various immunotropic preparations. The efficiency of the therapy was estimated according to the results of clinical observations, and the parameters of systemic immunity. Basic therapy included the appointment of rehydration, vasoactive drugs, vitamins of group B. In comparison groups children were given one of the following preparations: Amixin, Anaferon for children, Cycloferon, Viferon in addition to the basic treatment. The study demonstrated the benefits of complex treatment for enteroviral meningitis with immunomodulators before applying basic therapy. Total maximum effect was observed in the group with Anaferon for children.